Enterprise Risk Management Practices in Malaysian Small and Medium-Sized Enterprises: An Overview - Manas, Nadhrah; Zakuan, Norhayati; Saman, Muhamad Zameri Mat; Setapa, Mariam (Information Management and Business Review, 2024)
SMEs are crucial to the economic growth of many countries, particularly developing ones like Malaysia. SMEs have contributed significantly to economic growth but they also often struggle with problems related to poor management, which increases the risk of failure and closure. Effective risk management is essential in sustaining the long-term sustainability of SMEs and improving managerial performance. This study investigates the enterprise risk management (ERM) practices used by Malaysian SMEs in the manufacturing sector. The factors influencing the risk management behaviors and practices of SME manufacturing workers and their compliance with risk management protocols are examined in this study using a mixed-methods approach. This study focuses on employee behavior to better understand how organizational culture affects risk management techniques in SMEs. To design effective reward and recognition programs, this research also examines the psychological components of risk management while accounting for the organizational, societal, and financial challenges that followed the 2008 financial crisis. The study also examines the impact of organizational structure on the efficacy of risk management initiatives in small and medium-sized enterprises. The practical findings of the study are expected to demonstrate the extent to which ERM influences organizational effectiveness in Malaysia’s SME manufacturing sector. This study intends to equip industry participants with the knowledge and confidence necessary to implement ERM successfully in their operations by offering insights into the factors that encourage and impede ERM adoption and its impact on organizational performance. This research advances ERM practices among SMEs and strengthens Malaysian businesses’ resilience and risk awareness.